Non-EFL Students' Perception of Their Difficulties in Writing English Application Letter - Tira Nur Fitria (ELT Worldwide: Journal of English Language Teaching, 2022)
The objective of this study is to know the Non-EFL students' perception of their difficulties in writing an English application letter. This research is descriptive quantitative research. The subject of this study is 199 students from the fifth-semester of Non-EFL students of ITB AAS Indonesia especially Diploma Students are involved in this research. The result analysis shows the students’ perception toward English writing that writing is one of the most difficult English skills, English Job Application Letter' is an interesting topic, writing a job application letter in English is more difficult than writing a job application letter in Indonesian because there are many aspects to be considered such as grammar, vocabulary, spelling, and punctuation. The students have several difficulties in writing English application letters, such as 1) finding job vacancies in English. 2) understanding the contents of job vacancies in English. 3) understanding the elements of a job application letter from the opening, body, and closing of the letter in English. 4) Write the elements of a job application letter in English at the opening, body, and end of the letter. 5) choosing the appropriate vocabulary. 6) writing based on English grammar (for example writing sentences and selecting the appropriate tenses. 7) using correct punctuation. 8) writing a job application letter in Indonesian first and then translating it into English by using Google Translate. After writing an English application letter, the students agree that writing a job application letter can improve their English writing skills, know a lot of English vocabulary and understand English grammar well and correctly. 4) after writing a job application letter, the students can find English job vacancies easily, and they feel that it can be useful for their career in the future when applying for a job.